2022
DOI: 10.1007/s41324-022-00430-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of flood inundation with the cloud computing platform over vegetation cover of Ganga Basin during COVID-19

Abstract: Around the month of July 2020, the people suffering from the COVID-19 pandemic got added burden of disastrous floods. The current study tries to understand the impact of flood inundation on the vegetation cover across the Ganga Basin with the help of a cloud-based computing platform like Google Earth Engine (GEE) in a near real-time scenario. This offers a semi-automatic scheme with customized algorithms to process the large scale of datasets to further analyze and derive the required information from space-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Çelik 16 conducted a comparison between the C4.5 and C5.0 algorithms and found that the classification model built using the C5.0 algorithm exhibited lower misclassification rates and higher accuracy. The use of satellite-derived normalized difference vegetation index (NDVI) and EVI enables the assessment of the direct impact of floods on vegetation cover, offering an effective method for studying vegetation coverage 17 , 18 . Additionally, Dai et al 19 demonstrated that the evaluation of the influence of crop residues on vegetation index and vegetation cover estimation could be achieved by comparing enhancement values and vertical values using a 2-m pixel model and a three-dimensional radiative transfer model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Çelik 16 conducted a comparison between the C4.5 and C5.0 algorithms and found that the classification model built using the C5.0 algorithm exhibited lower misclassification rates and higher accuracy. The use of satellite-derived normalized difference vegetation index (NDVI) and EVI enables the assessment of the direct impact of floods on vegetation cover, offering an effective method for studying vegetation coverage 17 , 18 . Additionally, Dai et al 19 demonstrated that the evaluation of the influence of crop residues on vegetation index and vegetation cover estimation could be achieved by comparing enhancement values and vertical values using a 2-m pixel model and a three-dimensional radiative transfer model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, the interactions between floods and the COVID-19 pandemic have been studied in terms of flood management (Laksmi et al 2020 ; Aji et al 2021 ; Tripathy et al 2021 ; Izumi et al 2022 ; Tiwari et al 2022 ; Turay 2022 ), impact on human communities (Aura et al 2020 ; Sadique and Kamruzzaman 2021 ) or environmental impact (Ghosh et al 2022 ), flood risk perception (Mondino et al 2020 ; Zinda et al 2022 ), and disaster mitigation education (Suharini et al 2020 ). The number of studies regarding the impact of floods on COVID-19 infection rates is rather low (Quigley et al 2020 ; Han and He 2021 ; Mavroulis et al 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%